Bacteriological quality and prevalence of foodborne bacteria in broiler meat sold at live bird markets at Mymensingh City in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study assessed the bacteriological quality and prevalence of foodborne bacteria in raw broiler meat sold in Mymensingh City. Materials and Methods: Thigh and breast meat samples (n = 80) from broiler chickens were randomly collected from four live bird markets (LBM) in Mymensingh city for bacteriological analysis. To determine the bacteriological quality, a 10-fold serial dilution of the thigh and breast homogenate was made. Then, total viable count (TVC), total coliform count (TCC), Staphylococci, and Salmonella spp. counts were determined using plate count agar, MacConkey agar, Mannitol salt agar, and Salmonella-Shigella agar. Gram stain, biochemical testing, PCR assays, and cultural properties were used to identify the bacterial isolates. Results: The TVC in the broiler meat sample ranged between log10 8.30 ± 0.54 colony forming unit (CFU)/gm and log10 9.04 ± 0.26 CFU/gm. TCC was found between log10 5.53 ± 0.38 CFU/gm and log10 6.66 ± 0.80 CFU/gm. The mean Staphylococcal count was recorded between log10 4.64 ± 0.61 CFU/gm and log10 6.42 ± 0.53 CFU/gm, and the total Salmonella count ranged between log10 4.75 ± 0.08 CFU/gm and log10 5.69 ± 0.58 CFU/gm. The prevalence of Escherichia coli was the highest (43.2%), followed by Staphylococcus aureus (36.8%) and Salmonella spp. (20%), respectively. Conclusions: Data from this study indicated that the TVC and TCC of raw broiler meat sold at LBM exceed the permissible limits and are contaminated with foodborne bacteria, which might cause public health hazards.J. Adv. Vet. Anim. Res., 9(3): 405–411, September 2022http://doi.org/10.5455/javar.2022.i608